Vitamin D-3/vitamin K-2/magnesium-loaded polylactic acid/tricalcium phosphate/polycaprolactone composite nanofibers demonstrated osteoinductive effect by increasing Runx2 via Wnt/beta-catenin pathway - ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (ELSEVIER, 2021)
Vitamin D3, vitamin K2, and Mg (10%, 1.25%, and 5%, w/w, respectively)-loaded PLA (12%, w/v) (TCP (5%, w/ v))/PCL (12%, w/v) 1:1 (v/v) composite nanofibers (DKMF) were produced by electrospinning method (ES) and their osteoinductive effects were investigated in cell culture test. Neither pure nanofibers nor DKMF caused a significant cytotoxic effect in fibroblasts. The induction of the stem cell differentiation into osteogenic cells was observed in the cell culture with both DKMF and pure nanofibers, separately. Vitamin D3, vitamin K2, and magnesium demonstrated to support the osteogenic differentiation of mesenchymal stem cells by expressing Runx2, BMP2, and osteopontin and suppressing PPAR-gamma and Sox9. Therefore, the Wnt/beta-catenin signaling pathway was activated by DKMF. DKMF promoted large axonal sprouting and needle-like elongation of osteoblast cells and enhanced cellular functions such as migration, infiltration, proliferation, and differentiation after seven days of incubation using confocal laser scanning microscopy. The results showed that DKMF demonstrated sustained drug release for 144 h, tougher and stronger structure, higher tensile strength, increased water up-take capacity, decreased degradation ratio, and slightly lower Tm and Tg values compared to pure nanofibers. Consequently, DKMF is a promising treatment approach in bone tissue engineering due to its osteoinductive effects.
Keywords: Bone tissue engineering; Composite nanofiber; Osteoblast cell; DRUG-RELEASE; DIFFERENTIATION; PROLIFERATION; ACTIVATION; OSTEOBLAST; HYDROGELS; DELIVERY; FIBERS; PCL